Social and Population-Related Determinants in the Development of Small Towns in Poland - Janiszewska, Anna; Klima, Ewa (Olsztyn Economic Journal, 2019)
The demographic changes that have been occurring in Poland for several decades concern all cities and towns, including those with the lowest population number – up to 20 thousand inhabitants. The article proposes a quantitative analysis of selected phenomena related to population and society in small Polish towns. The two most crucial demographic issues of Polish urban units, depopulation and population ageing, were analysed with the use of simple typological methods. The analysis was conducted on the basis of available statistical data. Additionally, a spatial perspective on the issue was presented.